The Effect of Learning Videos on Students' Mathematical Abilities: A Meta-Analysis Study - Dinar Riaddin (EduMa: Mathematics education learning and teaching, 2022)
This study aims to determine the influence of learning videos on mathematical ability. The design used to test the research questions is a meta-analysis. Based on searches on the ERIC, SAGE, SpringerLink, and Google Scholar Databases, 28 measures of effect were found that met the specified inclusion criteria. Data analysis was carried out with the help of JASP 0.16.1.0 software. The results of the analysis showed that the use of learning video media had a major effect on mathematical ability when compared to conventional learning media (d = 1.12; p < 0.01). The results of the analysis based on moderator variables found that the influence of the flipped classroom model compared to conventional teaching on mathematics ability differed according to the level of education (Qb = 36.25; p < 0.05), and the measured ability (Qb = 15.7; p < 0.05), but did not differ according to the sample size group (Qb = 0.98; p > 0.05) and the year of study (Qb = 2.31; p < 0.05)